The factor structure of the peer-feedback orientation scale (PFOS): toward a measure for assessing students' peer-feedback dispositions. Issue 1 (17th January 2022) - Kasch, Julia; Van Rosmalen, Peter; Henderikx, Maartje; Kalz, Marco
Abstract: This study reports on the quantitative findings of an exploratory sequential mixed methods study in which the underlying factor structure of students' peer-feedback orientation (i.e. openness to provide and receive peer-feedback) was investigated. Building on the qualitative findings of a previous study in which the 'peer-feedback orientation' concept was introduced, an online survey was developed to collect data among higher education students ( N  = 148). An exploratory factor analysis produced a five-factor solution including the dimensions: accountability, communicativeness, utility, self-efficacy and receptivity. The practical value of the results lies in having a measure of students' peer-feedback orientation that provides teachers and researchers with an instrument for understanding students' dispositions toward receiving and providing peer-feedback.